Opportunity and benefits of functional food from the sea: A Rewiew - Paulus Damar Bayu Murti; Bambang Dwiloka; Ocky Karna Radjasa; James Ngginak (JURNAL SAINS NATURAL, 2021)
Functional food has been believed to prevent and reduce the possibility of chronic diseases such as obesity, diabetes, coronary heart disease, hypertension and cancer. The sea offers resources that can be used as a source of functional food. Research on bioactive compounds from marine life has been carried out, which have biological activity. For example, omega-3 consist of two types of acids, namely docosahexaenoic acid (DHA) and eicosapentanoic acid (EPA), which is contained in fish. Carotenoids and xanthophylls are abundant in macroalgae. Likewise with phenolic compounds and polysaccharides derived from algae. The protein hydrolysate from fish waste which is used as an alternative product has biological activity. Chitin and chitosan were extracted from crustacean shells and marine mollusk. Referring to the diversity of compound bioactivity from marine resources, this review emphasizes more on the potential of functional food ingredients owned by marine resources and their opportunities and benefits..Keywords: Functional food, Marine, Bioactive compounds, Chronic diseases, Biological activityABSTRAKPeluang dan manfaat pangan fungsional dari laut: Telaah PustakPangan fungsional telah dipercayai dapat mencegah dan menurunkan kemungkinan penyakit kronis seperti obesitas, diabetes, jantung koroner, hipertensi dan kanker. Laut menawarkan sumberdaya yang dapat dimanfaatkan sebagai sumber bahan pangan fungsional. Penelitian mengenai senyawa bioaktif dari biota laut sudah banyak dilakukan yang memiliki aktivitas biologis.  Sebagai contoh, Omega-3 terdiri atas dua jenis asam yaitu asam dokosaheksaenoat (DHA) dan asam eikosapentanoat (EPA) yang terkandung pada ikan. Karotenoid dan xantofil yang banyak terkandung pada makroalga. Begitu pun dengan senyawa fenolik dan polisakarida yang berasal dari alga. Hidrolisat protein dari limbah ikan yang dimanfaatkan sebagai produk alternatif memiliki aktivitas biologis. Kitin dan kitosan yang diekstrak dari limbah cangkang krustasea dan moluska laut. Mengacu pada keragaman bioaktivitas senyawa dari sumberdaya kelautan, review ini lebih menekankan pada potensi bahan pangan fungsional yang dimiliki oleh sumberdaya kelautan serta peluang dan manfaatnya.Kata kunci : Pangan fungsional, Laut, Senyawa bioaktif, Penyakit kronis, Aktivitas biiologi